BUILDING A PATTERN OF CULTURE AND THOUGHT FOR WORKERS IN AN OIL COMPANY THROUGH AN ESP PROGRAM ON THE CHALLENGE AGAINST POLLUTION - Kathem Qattous (European Scientific Journal, ESJ, 2014)
The notion of pollution is closely connected to the industrial and technological progress in the Western world. Researchers have mentioned that hazards of pollution have endangered the earth's ecological balance, human life, and the earth’s natural resources (air, water, and food). Aramco, an oil company operating in Saudi Arabia, has contributed to the environmental pollution in Saudi Arabia to a great extent. Saudi Arabia, being an oil producing country is been endangered by pollution, due to the activities of large numbers of factories and cars in the country. Therefore, Aramco has taken the responsibility for warring against pollution in different ways, including educating the employees through an ESP training program.This paper proposes that the company deemed it fit that its workers should be socialized using the American concept. This concept is with regards to the challenge against pollution in the company, country, and the world level as a whole. However, this was attained by building a pattern of culture and thought through an ESP training program known as VELT. The pattern has three steps: firstly, the awareness of the concept of pollution and Aramco’s responsibility towards the control of environmental pollution. Secondly, extensive knowledge about pollution, causes, results, dangers, and management; and thirdly, what actions to be taken to fight it and safeguard children, the environment, and the country of Saudi Arabia from the dangers through positive behavior.